Effective pupil dilatation with a mixture of 0.75% tropicamide and 2.5% phenylephrine: A randomized controlled trial - Trinavarat Adisak; Pituksung Auengporn (Indian Journal of Ophthalmology, 2009)
Purpose: To compare the efficacy in pupil dilatation between a mixture containing 0.75% tropicamide and 2.5% phenylephrine and the alternate application of 1% tropicamide and 10% phenylephrine eye drops. Material and Methods : Patients requiring pupil dilatation were randomized to receive one drop of the mixture every 10 min for four times or our standard application of one drop of 1% tropicamide alternating with one drop of 10% phenylephrine every 10 min for two cycles. Pupil size was measured under bright light with the pupil gauge before, and every 5 min after initial application for 40 min. Application of the drops was discontinued once the pupil diameter reached 7 mm. Blood pressure and pulse rate were monitored every 15 min. Results: Of 40 patients (age 57.3±10.9 years, range 35-70 years), 22 were randomized into the mixture group and 18 into the alternate drug group. Baseline pupil sizes were 1.7±0.5 mm in the mixture group and 1.8±0.4 mm in the alternate drug group. The pupils were successfully dilated to 7 mm within 40 min in 17 patients of the mixture group compared to seven patients in the alternate drug group ( P =0.004, Log Rank test). The mean pupil sizes at 40 min were 6.6±0.8 and 6.0±0.9 mm in the mixture and alternate drug groups respectively ( P =0.050, t-test). Blood pressure and pulse rate were stable and similar in both groups. Conclusions: The mixture of 0.75% tropicamide and 2.5% phenylephrine is superior to our standard application of 1% tropicamide alternating with 10% phenylephrine. It provides faster and more successful pupil dilatation within 40 min.